Studi Multi Situs: Pelaksanaan Pembelajaran Daring Synchronous dan Asynchronous Pada Sekolah Dasar di Jember - Alamsyahrony, Syahidi; Soetjipto, Budi Eko; Atok, A. Rosyid Al (JKTP: Jurnal Kajian Teknologi Pendidikan, 2023)
The purpose of this study is to thoroughly analyze the implementation of synchronous and asynchronous online learning in two elementary schools in Jember. The two schools are, Tiga Bahasa Rukun Harapan Elementary School, and Al Baitul Amien 01 Elementary School. This study used a qualitative multi-site study method. The data collected relates to planning online learning, implementing online learning, and evaluating the implementation of online learning. The data analysis technique begins with single-site data analysis followed by cross-site data analysis. The single site analysis procedure was carried out with the Miles & Huberman analysis model. The cross-site analysis procedure was carried out using an analytic induction model looking for the final cross-site findings. The results of the study show that in online learning planning, educators need to consider online learning principles that are easy for all students and teachers to follow as a first step in planning effective online learning. At the stage of implementing online learning, the important thing for the teacher to do is to organize the platform according to the type of online learning into a digital class that ideally approaches real learning conditions. In the evaluation of learning the teacher again ensures the ease of communicating with students, the suitability of the platform for the type of learning, the ease of accessing material, ensuring the level of authenticity of student answers, and the teacher can collaborate with parents to control student learning activities.Abstrak Tujuan penelitian ini menganalisis secara menyeluruh pelaksanaan pembelajaran daring synchronous dan asynchronous pada dua sekolah dasar di Jember. Kedua sekolah tersebut yaitu, SD Tiga Bahasa Rukun Harapan, dan SD Al Baitul Amien 01.  Metode penelitian yang digunakan yaitu kualitatif studi multi situs. Data yang dikumpulkan berkaitan dengan perencanaan pembelajaran daring, penerapan pembelajaran daring, dan evaluasi pelaksanaan pembelajaran daring. Teknik analisis data yang pertama menggunakan analisis data situs tunggal kemudian dilanjutkan dengan analisis data lintas situs. Prosedur analisis situs tunggal dilakukan dengan model analisis Miles & Huberman. Prosedur analisis lintas situs dilakukan dengan model induksi analitik mencari temuan akhir lintas situs. Hasil penelitian menunjukan pada perencanaan pembelajaran daring, pendidik perlu mempertimbangkan prinsip pembelajaran daring yang mudah diikuti oleh semua siswa dan guru sebagai langkah awal merencanakan pembelajaran daring yang efektif. Pada tahap penerapan pembelajaran daring hal penting yang dilakukan guru adalah mengorganisasikan platform sesuai jenis pembelajaran daring menjadi kelas digital yang idealnya medekati kondisi pembelajaran secara nyata. Pada evaluasi pembelajaran daring guru kembali memastikan kemudahan berkomunikasi dengan siswa, kesesuaian platform dengan jenis pembelajaran daring, kemudahan mengakses materi, memastikan tingkat keaslian jawaban siswa, dan guru dapat berkolaborasi bersama orangtua untuk mengontrol aktivitas belajar siswa.